The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5194/angeo-35-87-2017
|View full text |Cite
|
Sign up to set email alerts
|

An improved troposphere tomographic approach considering the signals coming from the side face of the tomographic area

Abstract: Abstract. The spatio-temporal distribution of atmospheric water vapour information plays a crucial role in the establishment of modern numerical weather forecast models and description of the different weather variations. A troposphere tomographic method has been proposed considering the signal rays penetrating from the side of the area of interest to solve the problem of the low utilisation rate of global navigation satellite system (GNSS) observations. Given the method above needs the establishment of a unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Therefore, the latter is obtained by subtracting the ZHD from ZTD. In our study, the observed multi-constellation GNSS data are processed using the multi-constellation GNSS precise point positioning (PPP) software with precise orbit and clock error products (Zhao et al, 2018). Consequently, the SWD can be expressed as follows:…”
Section: Gnss Tropospheric Tomographymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the latter is obtained by subtracting the ZHD from ZTD. In our study, the observed multi-constellation GNSS data are processed using the multi-constellation GNSS precise point positioning (PPP) software with precise orbit and clock error products (Zhao et al, 2018). Consequently, the SWD can be expressed as follows:…”
Section: Gnss Tropospheric Tomographymentioning
confidence: 99%
“…Therefore, the preliminary result concluded from those studies needs further verification based on the observed multi-constellation GNSS data. Although some tomographic experiments have been performed using the observed multi-GNSS observations (Benevides et al, 2017;Dong and Shuanggen, 2018;Zhao et al, 2018), the influence of station density and different combinations of multi-GNSS observations on troposphere tomography, which is the focus of this study, have never been well investigated. In this paper, a method is proposed to determine the optimal division of voxels in the horizontal direction automatically according to the range of the tomography area as well as the number and distribution of GNSS stations.…”
Section: Introductionmentioning
confidence: 99%
“…To solve this problem, Rohm and Bosy estimated the outer part of the signal rays using the UNB3m model based on a ray-tracing method [17], Notarpietro et al used European center for medium-range weather forecasts (ECMWF) data to calculate the SWV outside the research area [19], and Chen and Liu applied the numerical weather prediction (NWP) profile data to estimate the slant wet delay (SWD) outside the modeling area [20]. Benevides et al proposed a geometric linear method using an empirically exponential negative function to increase the utilization of signal rays [21], whereas Yao et al introduced a unit scale factor model and reconstructed a sophisticated model for considering the signal rays penetrating from the side face of the study area [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the GNSS tomography technique, the WR can also be retrieved by data assimilation which is based on numerical weather prediction (NWP) models (Perler et al, 2011b). The Weather Research and Forecasting (WRF) model is a state-of-the-art atmospheric modeling system that is used to simulate the dynamic processes of the atmosphere (Jankov et al, 2005;Carvalhoaabc, 2012). It is mainly developed and supported by the Mesoscale and Microscale Meteorology (MMM) Laboratory of the National Center for Atmospheric Research (NCAR).…”
Section: Introductionmentioning
confidence: 99%